Pengaruh Financial Distress, Total Asset Turnover, dan Audit Tenure pada Pemberian Opini Going Concern - Gani Damanhuri, Abdul; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 30 No 9 (2020), 2020)
The purpose of this study is to obtain empirical evidence of the influence of financial distress, total asset turnover, and audit tenure on going concern opinion. Research located on the Indonesia Stock Exchange (BEI) especially for the manufacturing sector for the period 2015-2018. The sample determined by using purprosive sampling technique, and obtained 23 companies as a samples with 4 years of observation so the total of sample it’s 92 samples. The hypothesis was tested using logistic regression analysis techniques. The test results reveal that financial difficulties have a significant effect on the implementation of opinion that is happening. Distributed TAT and tenure audits are negative on going concern opinion. Keywords: Financial Distress; Total Asset Turnover; Tenure Audit; Going Concern Opinion.